Human Rights in Occupied Tibet: A Succinct Study of Consistent Atrocities and Genocide (Journal of Political Science and International Relationship, 2025)
The discussion surrounding Tibet and China has been a prominent topic of global conversation for a considerable period of time. Tibetans have advocated for self-determination and engaged in nonviolent efforts to establish an independent state. Tibetans in exile have undertaken many initiatives to garner international assistance and backing, including the establishment of student organisations worldwide to advocate the restoration of their autonomous statehood, organising peaceful demonstrations against the Chinese government’s acts of violence, and engaging in writing endeavours to reinforce their objections. China flagrantly violates the Human Rights of Tibetans, posing a grave threat to the preservation of Tibetan culture. Nevertheless, the international community appears to be taking no action. Accusations of human rights breaches and deliberate cultural destruction are grave charges levelled against China. This could be termed cultural annihilation or cultural genocide in general terms, involving deliberate acts that go beyond the physical and biological dimensions of a population in the pursuit of destroying its broader institutions. The research will extensively examine cultural genocide, a heinous crime that warrants significant attention. However, this research encompasses more than just this aspect and also addresses other international legal norms. This research paper will examine critical human rights issues, including the deaths of political prisoners resulting from torture and lack of proper medical care, the People’s Republic of China’s failure to provide sufficient education, high child mortality rates, forced sterilizations, and maternal health concerns, especially in Tibetan areas. The paper will also explore religious persecution and the struggle for self-determination among Tibetans. This paper attempts to grossly analyse the violation by China on Human Rights of Tibetan people. This study will use a multi-dimensional methodological approach involving doctrinal and analytical strategies as well as qualitative fieldwork. Secondary materials engaged include books, research papers, and international reports. Historical analysis contextualized Tibet’s socio-political status before and after its annexation, while thematic categorization of issues such as religious freedom, resource exploitation, and cultural genocide provided a structured framework for analysis.